Fluorescent Pyranoindole Congeners: Synthesis and Photophysical Properties of Pyrano[3,2-f], [2,3-g], [2,3-f], and [2,3-e]Indoles - Ainur D. Sharapov; Ramil F. Fatykhov; Igor A. Khalymbadzha; Maria I. Valieva; Igor L. Nikonov; Olga S. Taniya; Dmitry S. Kopchuk; Grigory V. Zyryanov; Anastasya P. Potapova; Alexander S. Novikov; Vladimir V. Sharutin; Oleg N. Chupakhin (Molecules, 2022)
This paper reports the synthesis of four types of annulated pyranoindole congeners: pyrano[3,2-f]indole, pyrano[2,3-g]indole, pyrano[2,3-f]indole, and pyrano[2,3-e]indole and photophysical studies in this series. The synthesis of pyrano[3,2-f], [2,3-g], and [2,3-e]indoles involve a tandem of Bischler–Möhlau reaction of 3-aminophenol with benzoin to form 6-hydroxy- or 4-hydroxyindole followed by Pechmann condensation of these hydroxyindoles with β-ketoesters. Pyrano[2,3-f]indoles were synthesized through the Nenitzescu reaction of p-benzoquinone and ethyl aminocrotonates and subsequent Pechmann condensation of the obtained 5-hydroxyindole derivatives. Among the pyranoindoles studied, the most promising were pyrano[3,2-f] and [2,3-g]indoles. These compounds were characterized by moderate to high quantum yields (30–89%) and a large (9000–15,000 cm−1) Stokes shift. More detailed photophysical studies were carried out for a series of the most promising derivatives of pyrano[3,2-f] and [2,3-g]indoles to demonstrate their positive solvatochromism, and the data collected was analyzed using Lippert-Mataga equation. Quantum chemical calculations were performed to deepen the knowledge of the absorption and emission properties of pyrano[3,2-f] and [2,3-g]indoles as well as to explain their unusual geometries and electronic structures.